Decision making and uncertainty: The role of heuristics and experience in assessing a politically hazardous environment. (18th July 2014) - Maitland, Elizabeth; Sammartino, André
<x xml:space="preserve">Abstract</x> Heuristics have long been associated with problems of bias and framing error, often on the basis of simulation and laboratory studies. In this field study of a high‐stakes strategic decision, we explore an alternative view that heuristics may serve as powerful cognitive tools that enable, rather than limit, decision making in dynamic and uncertain environments. We examine the cognitive efforts of senior decision makers of an inexperienced multinational, as they assessed a potential acquisition in a politically hazardous African country. They applied a diversity of heuristics, some with clear building block rules, to build small world representations of this very uncertain strategic context. More expert individuals drew on experiential learning to build richer representations of the political hazard environment. Copyright © 2014 John Wiley & Sons, Ltd.